2013
DOI: 10.1021/jp402941u
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evolution of Fe–Mo Bimetallic Catalysts for Diameter and Density Modulation of Vertically Aligned Carbon Nanotubes

Abstract: Fe−Mo bimetallic catalyst is a promising candidate for achieving efficient growth and fine structures of vertically aligned carbon nanotubes (VA-CNTs) by catalytic chemical vapor deposition (CVD). Understanding the surface morphological evolution of a bilayer metal film and accompanied changes in the resultant CNT structure is a key to modulating the VA-CNT growth. We correlate the growth rates and individual CNT structures with the Fe−Mo catalyst morphological evolution. At CVD conditions, the layered bimetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 68 publications
1
16
0
Order By: Relevance
“…Later, Edgar et al [18], Jeon et al [19], Goss et al [20], Peng et al [21], demonstrated CNT growth by employing growth temperatures in the range of 880-1010°C without the use of additional catalyst promoters. The excessive growth temperatures required with FeMoC appear to counter previous work with Fe-Mo catalyst systems demonstrating CNT growth at temperatures as low as 550°C [22][23][24]. It should be noted that both Fe and Mo have been shown to be efficient catalysts both independently and as mixed metal nanoparticles [25][26][27][28][29][30]; thus, FeMoC should be ''active'' for CNT growth, but under the prior growth conditions studied it is not [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 78%
“…Later, Edgar et al [18], Jeon et al [19], Goss et al [20], Peng et al [21], demonstrated CNT growth by employing growth temperatures in the range of 880-1010°C without the use of additional catalyst promoters. The excessive growth temperatures required with FeMoC appear to counter previous work with Fe-Mo catalyst systems demonstrating CNT growth at temperatures as low as 550°C [22][23][24]. It should be noted that both Fe and Mo have been shown to be efficient catalysts both independently and as mixed metal nanoparticles [25][26][27][28][29][30]; thus, FeMoC should be ''active'' for CNT growth, but under the prior growth conditions studied it is not [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 78%
“…Other than the CVD conditions, researchers have long been interested in the catalyst engineering, given the fact that the CNT CVD is a heterogeneous catalysis process. One way of engineering the catalyst is to optimize the preparation method and tailor the composition such as mono- and bimetallic systems 24 25 26 . It is not only important to select the right catalyst material but also to prepare the catalyst properly in order to provide the desired nanoparticle morphology and stability.…”
mentioning
confidence: 99%
“…FeMoC was synthesized and purified as previously reported [14]. In a typical synthesis, iron(II) chloride tetrahydrate (1.00 g, 5.03 mmol) was dissolved in Millipore water (75 mL) followed by the addition of sodium molybdate dihydrate (2.00 g, 8.27 mmol).…”
Section: Femoc Synthesismentioning
confidence: 99%
“…Additionally, FeMoC belongs to the Fe-Mo system that consists of high temperature alloys, likely to maintain their structure under CCVD conditions. The Fe-Mo system has also demonstrated excellent catalytic performance; ultra-long single walled carbon nanotubes (SWCNT) growth (>18.5 cm), growth of ultra-high-density SWCNTs (160 SWCNTs/μm 2 ), and SWCNT growth under variable temperatures (450-1000 °C) [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%